Preparation of octenyl succinic anhydride-modified debranched starch vesicles for loading of hydrophilic functional ingredients. (September 2019) - Chang, Ranran; Xiong, Liu; Li, Man; Chen, Haihua; Xiao, Junxia; Wang, Shiqing; Qiu, Lizhong; Bian, Xiliang; Sun, Chunrui; Sun, Qingjie
Abstract: Vesicles have been attracting a great deal of interest because of their great potential for health food, medicine, and biotechnology applications. This study aimed to develop a new type of debranched starch (DBS) vesicle for loading and delivering active components. DBS with a low degree of polymerization (6.75) and good water solubility was modified with octenyl succinic anhydride (OSA) to obtain an amphiphilic polymer. Both the Fourier transform infrared spectroscopy and the 1 H nuclear magnetic resonance results confirmed the successful synthesis of amphiphilic OSA-DBS polymers. The OSA-DBS spontaneously formed 10–30 nm vesicles in a water system, as measured by transmission electron microscopy. The vesicles were relatively stable at different temperatures, pH values, and ionic strengths. Insulin was used as a hydrophilic functional ingredient model. The insulin-loaded vesicles exhibited a high loading content (∼13.36%). These OSA-DBS vesicles have potential utility as advanced carriers in the health food and biomedical industries. Graphical abstract: Image 1 Highlights: Soluble debranched starch (DBS) was modified by octenyl succinic anhydride (OSA). The OSA-DBS could self-assemble into vesicles with particle size of 10–30 nm. Insulin-loaded vesicles exhibited high loading content and sustained-release property.